A statistical survey of polar cap cold and hot patches in the Southern Hemisphere using a DMSP Satellite - Duan Zhang; QingHe Zhang; Kjellmar Oksavik; ZanYang Xing; L. R. Lyons; HuiGen Yang; Tong Xu; Marc Hairston; XiangYu Wang; YuZhang Ma; GuoJun Li; Yong Wang; et al. (Earth and Planetary Physics, 2025)
This paper is a statistical survey of Southern Hemisphere cold and hot polar cap patches, in relation to the interplanetary magnetic field (IMF) and ionospheric convection geometry. A total of 11,946 patch events were identified by Defense Meteorological Satellite Program (DMSP) F16 during the years 2011 to 2022. A temperature ratio of ion/electron temperature (Ti/Te) < 0.68 is recommended to define a hot patch in the Southern Hemisphere, otherwise it is defined as a cold patch. The cold and hot patches have different dependencies on IMF clock angle, while their dependencies on IMF cone angle are similar. Both cold and hot patches appear most often on the duskside, and the distribution of cold patches gradually decreases from the dayside to the nightside, while hot patches have a higher occurrence rate near 14 and 21 magnetic local time (MLT). Moreover, we compared the key plasma characteristics of polar cap cold and hot patches in the Southern and Northern Hemispheres. The intensity of the duskside upward field-aligned current of patches in the Southern Hemisphere (SH) is stronger than that in the Northern Hemisphere (SH), which may be due to the discrepancy in conductivities between the two hemispheres, caused by the tilted dipole. In both hemispheres, the downward soft-electron energy flux of the dawnside patches is significantly greater than that of the duskside patches.